Synergistic effects of non-thermal plasma and plasma-activated water on germination, water uptake, and early growth of diverse crop seeds - Rajesh Prakash Guragain; Deepesh Prakash Guragain; Hom Bahadur Baniya; Deepak Prasad Subedi (Results in Engineering, 2025)
This study investigates the combined effect of non-thermal plasma (NTP) seed treatment and plasma-activated water (PAW) irrigation on seed germination, imbibition dynamics, and seedling growth in five crop species: barley, mustard, garden cress, buckwheat, and carrot. Seeds were exposed to atmospheric argon plasma for 3 min, and PAW was prepared by treating deionized (DI) water with gliding arc discharge plasma for 5 and 10 min. Physicochemical analysis revealed significant changes in PAW properties with increasing plasma exposure time. Multiple germination indices—germination percentage, mean germination time (MGT), coefficient of velocity of germination (CVG), germination index (GI), and germination value (GV) -demonstrated significant improvement in NTP+PAW irrigated seeds. Barley and carrot exhibited the highest germination enhancement (up to 88–89 %), with corresponding reductions in MGT and increases in GI and CVG. NTP treatment also caused minor mass loss (0.11–0.83 %) across seed types, attributed to etching effects and seed coat modification. Imbibition studies revealed enhanced water uptake in NTP + PAW-irrigated seeds, especially during mid- to late soaking phases (4–10 h), with mustard and carrot showing increases up to 55.88 % and 35.42 %, respectively. Additionally, seedling growth and vigor were significantly enhanced by NTP+PAW, with mustard showing the highest increase in seedling length (up to 204.6 % in vigor and 173 % in length) under NTP+PAW (10 min). These findings highlight the synergistic benefits of NTP and PAW in modifying seed surface properties, promoting rapid water uptake, and stimulating physiological responses via RONS. The study supports plasma-based seed treatment as a sustainable, eco-friendly alternative to conventional priming methods, with potential applications in precision agriculture and climate-resilient farming.